Association Between Coffee Drinking Frequency and Sugar Intake with Adolescents Nutritional Status - Vivilia Niken Hastuti; Khoirul Anwar; Aulia Putri Astuti (Ikatan Sarjana Gizi Indonesia (ISAGI), 2025)
Nutritional status, especially overnutrition in adolescents, is a multifactorial problem, including the influence of peers, lifestyle, and the amount of pocket money that affects diet. The frequency of coffee consumption with high sugar content is a habit that many adolescents have that can affect their nutritional status. This study aims to analyze the relationship between frequency of coffee consumption and sugar intake on the nutritional status of students at SMAN 50 Jakarta. This study was observational in nature using a cross-sectional research design. A total of 97 respondents were obtained using purposive sampling technique. Data were collected using questionnaires related to respondent characteristics, frequency of coffee consumption, sugar intake, and nutritional status. The relationship between dietary coffee consumption and sugar intake on nutritional status was tested using the Spearman test. The results of this study are the majority of respondents 55.68% often consume coffee, 80.41% of respondents consume excess sugar derived from coffee consumption. Nutritional status is mostly distributed into the normal category (46.3%). Respondents who experienced undernutrition status amounted to 15.4%, and overnutrition amounted to 20.6% and obesity amounted to 17.5%. There is a significant relationship between the frequency of coffee consumption (p<0.001) and sugar intake from coffee (p<0.001) on the nutritional status of adolescents.